2017
DOI: 10.1021/acs.energyfuels.6b01735
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Behavior of the Black Liquor Derived from Soda–Anthraquinone and Soda–Oxygen Pulping of Rice Straw at Different Reaction End Points

Abstract: Black liquor (BL) with inorganic cooking chemicals and combustible material is the alkali and power resources for pulping. For rice straw pulping, BL obtained from soda–anthraquinone (AQ) pulp (SABL) could hardly be combusted in a traditional recovery furnace, because of the involvement of a great deal of silica in it. On the contrary, soda–oxygen pulping may have the majority of the silica depositing in pulp owing to the oxidation, instead of its dissolution in the BL (SOBL). The pyrolysis behavior of SOBL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…However, because of the hydrogen-bonding interaction that occurred when the treated straw was air-dried, the loosened tissue collapsed, shrank, and adjacent fibrous bands closed up, and thus, the excessive addition of lye could bring about structural collapse. Unlike pretreatment with moderate NaOH loading (below 14%), after pretreatment with highly concentrated NaOH solution, the straw could not keep its original structure, which has been shown in our previous work [ 17 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, because of the hydrogen-bonding interaction that occurred when the treated straw was air-dried, the loosened tissue collapsed, shrank, and adjacent fibrous bands closed up, and thus, the excessive addition of lye could bring about structural collapse. Unlike pretreatment with moderate NaOH loading (below 14%), after pretreatment with highly concentrated NaOH solution, the straw could not keep its original structure, which has been shown in our previous work [ 17 ].…”
Section: Discussionmentioning
confidence: 86%
“…Our previous paper [ 17 ] presented a study of the soda extraction of wheat straw using a wider range of NaOH dosages under low-temperature conditions (90 °C). We found that soda extraction has the advantage of selective dissolution of lignins, whilst carbohydrates were retained.…”
Section: Introductionmentioning
confidence: 99%
“…After cooking, centrifugation was used to separate BL from the pulp and then washed BL with hot water three times. The detail information was act in accordance with our previous work (Zhang et al 2017).…”
Section: 2preparation Of the Blmentioning
confidence: 99%
“…Thus, the latter is superior to the former in terms of BL features. However, the lack of research on BL characteristics following treatment in a recovery furnace still confused the application on the alkali and energy recovery (Jafari et al 2014;Zhang et al 2017). Investigating the properties of the BL obtained from wheat straw pulping is an important endeavor.…”
Section: Introductionmentioning
confidence: 99%
“…A dissolution process of silica in the alkaline solution can be explained by the formation of silicate. A high silicate content may cause serious silicon scaling during evaporation and concentration of alkali liquor and thus reduces alkali recovery efficiency (Zhang and Chen 2017). According to Xu and Li (2013), when the silicon content is in the range of 0.15% to 0.54%, which is equivalent to the silicon content in wood pulping black liquor, there is no obvious silicon interference.…”
Section: Pretreatment Solution Analysismentioning
confidence: 99%